Mädchenbildung im früheren Geographieunterricht: Ein vergessenes Stück preußisch-deutscher Bildungsgeschichte - Schultz, Hans-Dietrich (Journal of Geography Education, 2006)
Taking the example of the education of girls in Germany and especially Prussia in former times, the essay is to show that it is useful for geography education as a modern field of research to keep in touch with its history. All in all, recent geography is estimated positively by male and female students, with the boys giving an even more positive estimation than the girls. In former times, geography used to be an unpopular subject, as an extensive investigation of interests from the beginning of the 20th century shows, which nearly is fallen into oblivion today. It has been forgotten, too, that early representatives of the older didactics of geography used to have very clear conceptions of gender differences, which can be reduced to the statement that girls were more emotional and boys more rational. This is in line with another assertion saying that boys were more interested in matters of physical geography and economic geography, while girls were more interested in matters concerning culture and ethnography. Anyway, an increase of differences was perceived. Comparing the former conceptions concerning gender-specific interests with results of today's empirical research, an astounding correspondence can be detected, which still has to be explained. Provided that the differences are persistent, the urgent question for teaching is how to deal with these differences. One of the recommendations is to be considerate of the differences, but to aim at an equalisation, because boys and girls live in the same world with the same phenomena. In former times, those who where involved in the education of teachers of geography had a similar view and rejected the idea of a restricted "kitchengeography" for girls. A particular case is the holistic geography of landscape of the 1920s which turns out to be of psychoanalytical treatment.